METHODOLOGICAL PRINCIPLES OF THE ORGANIZATION OF REAL ESTATE OBJECTS IN THREE-DIMENSIONAL CADASTЕRS - Meteshkin К.; Kondraschenko О.; Nesterenko, S.; Radzinska, Y. (Municipal economy of cities. Series: «Economy science», 2023)
The purpose of the article is to study methodological provisions for the organization of real estate objects in the three-dimensional cadastre. The principles of combining two-dimensional information about land plots and three-dimensional information about real estate objects, taking into account legal information about each element of the system, are determined. Special attention is paid to the principles of selection and implementation of the geospatial data base of the three-dimensional cadastre system. This database of geospatial data is based on modern developments and effective tools. The three-dimensional cadastral system is responsible for registering the legal status of real estate objects and has the ability to provide this information to clients in the future. The increase in the use of space under and above the surface of the Earth presented the cadastral system with the need to determine and store information about objects of the real world under and above the surface. Entitlement to specified objects is still registered using 2D surface areas. In the third dimension, it is important to be able to penetrate into the actual situation, which is determined by the factor of confirming the legal status of the land plot or real estate object. Therefore, the developed three-dimensional cadastre system provides an opportunity to collect, model and store, request and visualize data on real estate objects under and above the surface in combination with already existing two-dimensional data on land plots. With the help of the specified proposals of the tool of the three-dimensional cadastral system, it is possible to use real estate objects more effectively, taking into account rights and restrictions. Thus, the study presents methodical regulations on the organization of real estate objects in the three-dimensional cadastre. The principles of combining two-dimensional information about land plots and three-dimensional information about real estate objects, taking into account legal information about each element of the system, are determined. Special attention is paid to the principles of selection and implementation of the geospatial data base of the three-dimensional cadastre system. This database of geospatial data is based on modern developments and effective tools. To access data and view query results, a viewer will be built on top of the geospatial database. It also looks at how data can be viewed administratively: as two-dimensional (traditional GIS interface) and three-dimensional (perspective, stereo) and in combination with each other in the same environment. The studied provisions make a significant contribution to the development of cadastral systems, the formation of cadastral data, the creation and management of geospatial databases of three-dimensional cadastre.